The Effect of Perceived Brand Foreignness, Perceived Brand Quality, and Perceived Brand Prestige toward Purchase Intention of EXCELSO in Pontianak - Audia, Audia Paramitha B1024131004 (Jurnal Manajemen Update, 2018)
Perceived Brand Foreignness has been used mostly in developing country. Therefore, it is proven by many companies using foreign-sounding brand names. As the implications, there are a lot of products on the market using foreign brand names despite the fact that these products are local product. The perceived quality that comes from foreign brand name create the image of superior quality than local brand name in consumerâ€™s mind. The superior quality image created by foreign brand name will affecting the intention to make the purchasing of the product. This study aims to examine the effects of Perceived Brand Foreignness, Perceived Brand Quality, and Perceived Brand Prestige in the context of Purchase Intention of EXCELSO in Pontianak.The sample of this study consists of 100 respondents who having fixed income and never made any purchasing of EXCELSO products before. The data were analysed in Structural Equation Model and Path Analysis using SmartPLS 3.0 software. It is found that Perceived Brand Foreignness shows positive effect on Perceived Brand Quality, Perceived Brand Prestige and Purchase Intention. Perceived Brand Quality also has positive effect on Purchase Intention. Meanwhile, Perceived Brand Prestige does not have effect on Purchase Intention. The result implies as partially mediation, where Perceived Brand Quality is mediate the influence of Perceived Brand Foreignness on Purchase Intention.Â Keywords: Perceived Brand Foreignness, Perceived Brand Quality, Perceived Brand Prestige, Purchase Intention